2010
DOI: 10.4103/0974-9233.65495
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical management of optic disc pit maculopathy without internal membrane peeling

Abstract: Optic disc pit is an excavation of the optic nerve head usually seen in association with other abnormalities of the optic nerve, peripapillary retina, or posterior vitreous detachment. In 50% the cases, it might be associated with serous macular detachment. The prevailing theory that explains this disorder is that subretinal fluid which is derived from liquefied vitreous passes through the optic disc pit and elevates the macula. In this study, we report a case of serous macular detachment complicating optic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Their results were consistent with ours; however, we achieved earlier improvement of CDVA and CMT. 10 Imamura et al and Young et al also performed interventional studies for ODP-M. 8,9 They found that the average duration for CDVA improvement ranged from 2 months to 8 months and that a flat, stable retina could be achieved for 1 year. Their techniques comprised pars plana vitrectomy, various methods for the creation of posterior vitreous face detachment, peeling of the ILM, laser treatment on the temporal edge of the disk, and intravitreal gas injection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their results were consistent with ours; however, we achieved earlier improvement of CDVA and CMT. 10 Imamura et al and Young et al also performed interventional studies for ODP-M. 8,9 They found that the average duration for CDVA improvement ranged from 2 months to 8 months and that a flat, stable retina could be achieved for 1 year. Their techniques comprised pars plana vitrectomy, various methods for the creation of posterior vitreous face detachment, peeling of the ILM, laser treatment on the temporal edge of the disk, and intravitreal gas injection.…”
Section: Discussionmentioning
confidence: 99%
“…Diab et al 10 reported the use of vitrectomy and gas injection without ILM peeling to treat a 36-year-old man with optic disk pit-related maculopathy. This showed success at 3 months postoperatively, and they reported improvement of CDVA to 20/100 (from 20/1000 at 2 months preoperatively), as well as reduction in CMT to 474 µ m (from 708 µ m preoperatively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible side effects of laser photocoagulation near the disc include paracentral scotomas, no change in visual acuity, and a low success rate in the resolution of serous macular detachment. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%